Fall of giants - Follett, Ken. (New York : Dutton, 2010)
Follows the fates of five interrelated families -- American, German, Russian, English, and Welsh -- as they move through the dramas of the First World War, the Russian Revolution, and the struggle for women's suffrage.
Map on lining papers.
Keywords: Twentieth century -- Fiction; World War, 1914-1918 -- Fiction; Great Britain -- History -- George V, 1910-1936 -- Fiction; Great Britain -- Social life and customs -- 1918-1945 -- Fiction; Soviet Union -- History -- Revolution, 1917-1921 -- Fiction; United States -- History -- 1913-1921 -- Fiction; Germany -- History -- 1918-1933 -- Fiction; Historical fiction; Domestic fiction; Epic fiction